Feed The World - Biological & Agricultural Engineering Research - Manougian, Eric J.; White, Patrick W.; Hallaq, Tom G. (Kansas State University, 2018)
Dr. Sharda and his colleagues and students do work in precision agriculture to increase efficiency of farming through innovations in farm machinery, sensors and technology, and agronomic algorithm development. We want to get the word out about this research to the public, farming stakeholders, and potential industry partners.
Keywords: Ajay Sharda